PELATIHAN PIJAT AKUPRESUR UNTUK UPAYA PREVENTIF DAN PROMOTIF KESEHATAN KELUARGA - Onny Priskila; Laili Mufida; Desi Hidayati; Rini Hamsidi; Ario Imandiri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Acupressure is a complementary non-pharmacological therapy that has the potential to be applied as a preventive and promotive health approach at the family and community levels. However, public knowledge and skills related to the proper and safe application of acupressure remain limited. This community service program aimed to improve community knowledge, skills, and awareness regarding self-acupressure techniques for maintaining family health. The activity was conducted in Randubener Village, Lamongan Regency, through collaboration between the Acupuncture and Herbal Medicine Study Program of Universitas Katolik Darma Cendika and the Traditional Medicine Study Program of Universitas Airlangga. The methods used included interactive lectures, demonstrations, hands-on practice, and evaluation using pre-test and post-test questionnaires. A total of 60 participants took part in the program. The results showed a significant increase in participants’ knowledge after the intervention, with the mean score rising from 5.4 in the pre-test to 8.9 in the post-test. Participants were able to identify basic acupressure points and apply simple acupressure techniques independently. In conclusion, the acupressure training program was effective in enhancing community knowledge and skills and contributed to strengthening community independence in preventive and promotive family health efforts.